2D graphitic-C3N4 hybridized with 1D flux-grown Na-modified K2Ti6O13 nanobelts for enhanced simulated sunlight and visible-light photocatalytic performance. Issue 18 (24th August 2017) - Wang, Qiang; Guan, Shiyou; Li, Bing
Abstract : Novel 1D/2D hybrid Na-K2 Ti6 O13 /g-C3 N4 heterojunction photocatalysts with enhanced simulated sunlight and visible-light photocatalytic performance have been successfully fabricated using a facile mixing–calcination method. Abstract : Two-dimensional (2D) graphitic-C3 N4 (g-C3 N4 ) was successfully hybridized with one-dimensional (1D) flux-grown Na-modified K2 Ti6 O13 nanobelts (Na-K2 Ti6 O13 NBs) for the first time to construct novel 1D/2D Na-K2 Ti6 O13 /g-C3 N4 heterostructured photocatalysts using a facile mixing–calcination method. The heterostructured Na-K2 Ti6 O13 /g-C3 N4 composites with three-dimensional (3D) hybrid architectures exhibited a remarkably enhanced photocatalytic efficiency for organic pollutant degradation in comparison with pure Na-K2 Ti6 O13 and g-C3 N4 under both simulated sunlight and visible-light irradiation ( λ > 420 nm), which could be mainly attributed to the synergistic effects between Na-K2 Ti6 O13 and g-C3 N4 including more efficient interfacial charge transfer, longer lifetimes and the stronger oxidation and reduction ability of photogenerated charge carriers, fundamentally originating from the formation of Na-K2 Ti6 O13 /g-C3 N4 heterojunctions based on the well-matched energy-band structures. Moreover, the Na-K2 Ti6 O13 /g-C3 N4 hybrids showed good stability and reusability for the photocatalytic degradation of organic pollutants. Finally, the possible mechanisms responsible for the improved simulated sunlight and visible-light photocatalytic performance were also investigated, respectively, based on the results of PL spectra, time-resolved fluorescence decay spectra, radical species trapping experiments, ESR spectra and PL-TA measurements. Overall, this work will not only be beneficial for the design and development of more efficient visible-light-responsive g-C3 N4 -based composites for solar energy conversion and environmental remediation but will also be influential in optimizing the visible-light photocatalytic activity of wide-band-gap 1D titanate nanomaterials to meet the requirements of practical applications.